Explorando os operadores argumentativos no ensino fundamental: uma prática que desafia o professor de língua portuguesa - San, Josuel Huang Pak (2024)
Argumentative operators are grammatical resources responsible for showing the argumentative force of statements and the meaning they point to (KOCH; ELIAS, 2022). They function as clues for sequential cohesion, since in addition to linking the parts of the text, they reinforce important semantic links between them. However, when we read the texts produced by our students, we noticed little use of them and a preference for the generic operator and to link sentences and establish various meaning relationships. Considering that there are differences in the use of argumentative operators depending on the type of text, the degree of formality and the register (speech and writing) and that we, as Portuguese language teachers, have the task of contributing to the development of our students' linguistic competence, we established an action-research project along the lines proposed by Profletras (AZEVEDO; FREITAG, 2020), to create a didactic module to stimulate the recognition of oppositional argumentative operators and expanding their repertoire in terms of these linguistic elements. To expand the repertoire of argumentative operators of 9th graders at Escola Municipal Coronel Sabino Ribeiro, located in the municipality of Maruim, in the state of Sergipe, a didactic module divided into four stages was developed. The first stage consisted of applying a reading comprehension protocol together with a text that was missing argumentative operators. The diagnosis of the class's reading proficiency followed the protocols being developed as part of the project “Impacts of the COVID-19 pandemic on children's and adults' language: a focus on the development and learning of reading”, with the cloze test diagnostic protocol (CARDOSO et al., 2023), and in addition to the diagnosis of a low level of reading comprehension, we identified the predominant use of the conjunction and to mark semantic relationships. For the second and third stages, we selected six texts based on the criteria of gradual visual and verbal information. Activity 1 of this sequence encourages the production of a written narrative based on two texts with a predominance of visual language. Activity 2 fosters reflection on using argumentative operators through four texts with a gradual mix of visual and verbal information. In the first two texts of this last activity, there is an articulation between the two types of language, while the previous two selected texts are short with extensive use of verbal language. We found that the activities in the didactic module favor the development of the skill proposed by the BNCC of “Using when writing/re-writing argumentative texts, linguistic resources that mark the relationships of meaning between paragraphs and statements in the text and connection operators appropriate to the types of argument and the way argumentative texts are composed” (BRASIL, 2018, p.145). The results of the application of our module, in convergence with Rocha's (2018) work developed at PROFLETRAS, which used visual language to explore temporal circumstantials, showed progress in the students' performance about the content worked on.